Simulation and experimental research on the wear of synchronous quadruple rotor of an internal mixer during the mixing process. (September 2022) - Han, Deshang; Zhang, Shoufeng; Pan, Yi; Wang, Chuansheng
Highlights: In this study, based on the viscoelastic solid theory of the rubber mixing process and the friction mechanism between rubber and metal, combined with the discrete element method, a dynamic simulation model for the wear of the synchronous quadrilateral rotor of an internal mixer is established. The simulation results are compared under different mixing parameters. Analysis is performed, and a control experiment is set up to verify the feasibility of the discrete element software (EDEM) rotor wear dynamic simulation model. Abstract: As the core component of an internal mixer, the rotor is subjected to friction from rubber and its filler during the mixing process, which causes the surface of the rotor to wear and can also affect the gap between the rotor edges as well as the gap between the rotor and the mixing chamber wall. The more significant the rotor wear, the larger the gap between the rotor ribs and the wall of the mixing chamber, which results in weaker shearing effect of the rotor on the rubber and even leads to uneven dispersion of filler in the rubber, eventually affecting the mixing effect and mixing quality of the glue. In this study, based on the viscoelastic solid theory of the rubber mixing process and the friction mechanism between rubber and metal, combined with the discrete element method, a dynamic simulation model for the wear of the synchronous quadrilateral rotor of an internal mixer is established. The simulations are performed in the EDEM software, and the results are analyzed and compared under different mixing parameters. Further, a control experiment is established to verify the feasibility of the proposed dynamic model for rotor wear.